Investigating the Complementary Polysemy and the Arabic Translations of the Noun Destruction in EAPCOUNT - Salhi, Hammouda (Meta, 2013)
This article investigates a topic at the intersection of translation studies, lexical semantics and corpus linguistics. Its general aim is to show how translation studies can benefit from both lexical semantics and corpus linguistics. The specific objective is to capture the semantic and pragmatic behavior of the noun destruction and its different translations into Arabic. The data are obtained from an English-Arabic parallel corpus made from UN texts and their translations (EAPCOUNT). The analysis of the data shows the polysemy of the word destruction as a number of semantic and pragmatic alternations can be captured. These findings are discussed in the frame of the Generative Lexicon (GL) theory developed by James Pustejovsky. The paper concludes with some concrete suggestions on how to enhance the relationship between linguists and translators and their mutual cooperation.